2018
DOI: 10.1556/1646.10.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of Charlson comorbidity index with stent restenosis and extent of coronary artery disease

Abstract: ObjectivesThe objective of this study is to investigate the effect of comorbid conditions [Charlson comorbidity index (CCI)] on stent restenosis who underwent coronary angioplasty earlier.MethodsPatients were divided into two groups; patients with critical restenosis [recurrent diameter stenosis >50% at the stent segment or its edges (5-mm segments adjacent to the stent) (Group 1; n = 53, mean age: 63.8 ± 9.9 years)] and patients with no critical restenosis [<50% obstruction (Group 2; n = 94, mean age: 62.1 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Among the top predictors were features that represent traditional cardiovascular risk factors, such as age, male sex, and hypertension. The Charlson Comorbidity Index had high importance in both models; previously, it has been correlated with recurrence and mortality following acute coronary syndromes 56,57 , as well as anatomic severity of coronary artery disease 58 . Features such as increased serum glucose, which is associated with a higher risk in our models, may better assess IHD risk than the diagnosis of diabetes alone, a feature that was not salient among the SHAP analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Among the top predictors were features that represent traditional cardiovascular risk factors, such as age, male sex, and hypertension. The Charlson Comorbidity Index had high importance in both models; previously, it has been correlated with recurrence and mortality following acute coronary syndromes 56,57 , as well as anatomic severity of coronary artery disease 58 . Features such as increased serum glucose, which is associated with a higher risk in our models, may better assess IHD risk than the diagnosis of diabetes alone, a feature that was not salient among the SHAP analysis.…”
Section: Discussionmentioning
confidence: 95%
“…CCI has been extensively investigated in various clinical conditions and its significance as a prognostic indicator has been demonstrated. A previous study depicted that CCI was higher in patients with a more diffuse extent of CAD than those with milder disease [ 30 ]. Rashid et al indicated that CCI >2 significantly increased the risk of mortality in acute coronary syndrome [ 31 ].…”
Section: Discussionmentioning
confidence: 99%